Lentinula edodes : AN EFFECTIVE ANTIMICROBIAL CONTROL AGAINST PLANT PATHOGENS - A REVIEW - PANT, AAUSHI; JOSHI, PARUL; SINGH, KHILENDRA; CHAMOLI, VIDHI; SUMAN, MEGHA; GAUR, KAMAKSHI; DHAMI, , BHAWANA; VERMA, SAKSHI; UNIYAL, NAVENDRA (The Bioscan, 2023)
In considering the enormous rise in the occurrence of diseases resistant to antibiotics, it is crucial to consider alternative therapies. The main causes of significant losses each year in plant are diseases are fungi, bacteria, viruses, and nematodes. Bio control agents can therefore be employed to treat these plant pathogens and enhancing the positive responses of plants. These biocontrol agents are an alternate approach to manage plant diseases that will help to minimise the overuse of agricultural pesticides. Lentinula edodes an edible mushroom has antimicrobial property against different plant pathogen and can play a role of effective biocontrol agent. They produce volatile chemicals that have a direct harmful impact on pathogens. They reduce the use of chemicals, less phyto toxic and improve soil health.